Predicting academic success using entry-level english proficiency scores - Umadevi, S.; Mohd Said, Rozzana (2012)
Lecturers teaching in the physiotherapy programme of the Health Science Faculty Of UiTM, are appalled at the high attrition rate of students in in Physiology and Anatomy in the first year and at the inability of many students to answer examination questions accurately without reproducing tracts of irrelevant information. Students' written answers often do not reflect the complexities in the workings of a physiological mechanism. Aside from a lack of motivation or a deficit in the ability to recall, synthesize or analyse information, they wondered to what extent this inability could be due to their lack of language proficiency which might impede their ability to comprehend the texts and to express themselves. Hence this study which is a collaboration between language and content-area lecturers, attempted to determine whether there is a correlation between language proficiency levels and academic performance. It attempted to correlate entry level MUET scores of students enrolled in the physiotherapy programme of the Health Science Faculty of UiTM and their first semester GPA scores. The MUET is used in Malaysian universities as an entry requirement for language proficiency. Though MUET is designed only to measure language proficiency levels and is not meant as a gauge to predict academic performance, can it actually foretell how a student would do in his or her content area subjects? The study was inconclusive because there wasn't a good spread of students in the different bands ie most students were either in band 3 or 4. There was not a sufficient number of students in band 2 or 5 or 6 in the Physiotherapy programme to enable us to do correlational studies. What we did find is that if students are admitted with a band 3, it can be expected that they would have a GPA of less than 2 in core subjects in their first semester.